High diastereoselectivity induced by intermolecular hydrogen bonding in [3 + 2] cycloaddition reaction: experimental and computational mechanistic approaches. (8th September 2016) - Yıldırım, Ayhan; Kaya, Yunus
Abstract: A diastereoselective [3 + 2] cycloaddition of N ‐aryl substituted maleimides with N, α ‐diphenyl nitrone possessing 11‐hydroxyundecyloxy as a flexible substituent was performed. Experimental and comprehensive mechanistic density functional theory studies reveals that intermolecular H‐bonding and steric repulsive interaction predominate exo‐Z and exo‐E cycloaddition transition states, respectively. The reaction proceeded smoothly depending on the reactants and gave a good yield of ( syn ) cis ‐isoxazolidine or ( anti ) trans ‐isoxazolidine as a single diastereomer. Abstract : A diastereoselective [3 + 2] cycloaddition was performed. H‐bonded transition state provides a single cycloadduct. Density functional theory calculations reveal that [3 + 2] cycloadditions maybe proceeded via one step, but strong asynchronous mechanism.